Cloning and expression of the Escherichia coli K-12 sad gene. - Marek, L E (1988)
The Escherichia coli K-12 sad gene, which encodes an NAD-dependent succinic semialdehyde dehydrogenase, was cloned into a high-copy-number vector. Minicells carrying a sad+ plasmid produced a 55,000-dalton peptide, the probable sad gene product.